The Legal Substance of Normative Ambiguity in Corporate Criminal Liability for Corruption - Mochamad Ananda Wyman Wahid; Hartiwiningsih Hartiwiningsih (Prosiding Seminar Nasional Ilmu Pendidikan, 2024)
The corporate criminal culpability concept is point by point in Article 20, passage (1) of Law Number 31 of 1999 on the Annihilation of Debasement, as revised by Law Number 20 in 2001. Concurring to this article, on the off chance that a enterprise locks in in debasement, both the organization and/or its administration can confront criminal charges. The term "and" implies a cumulative approach, holding both the corporation and its management accountable simultaneously, whereas "or" implies an alternate method, holding either the corporation or its management answerable. The usage of "can" generates ambiguity because its application is dependent on the interpretation of prosecutors and judges. Authoritative, conceptual, and case think about techniques were utilized to conduct the investigate. The information infer that Article 20, passage (1) of the PTPK Law is subject to numerous elucidations, coming about in regulating equivocalness. This is aggravated by the absence of precise standards for determining criminal responsibility for either the organization, its management, or both. This leads to conflicting legal applications by judges, resulting in legal confusion. Hence, it is required to reexamine the corporate risk demonstrate for debasement charges beneath Article 20, passage (1) of the PTPK Law.